Chemical Quantification of Atomic-Scale EDS Maps under Thin Specimen Conditions. (13th October 2014) - Lu, Ping; Romero, Eric; Lee, Shinbuhm; MacManus-Driscoll, Judith L.; Jia, Quanxi
Abstract We report our effort to quantify atomic-scale chemical maps obtained by collecting energy-dispersive X-ray spectra (EDS) using scanning transmission electron microscopy (STEM) (STEM-EDS). With thin specimen conditions and localized EDS scattering potential, the X-ray counts from atomic columns can be properly counted by fitting Gaussian peaks at the atomic columns, and can then be used for site-by-site chemical quantification. The effects of specimen thickness and X-ray energy on the Gaussian peak width are investigated using SrTiO3 (STO) as a model specimen. The relationship between the peak width and spatial resolution of an EDS map is also studied. Furthermore, the method developed by this work is applied to study cation occupancy in a Sm-doped STO thin film and antiphase boundaries (APBs) present within the STO film. We find that Sm atoms occupy both Sr and Ti sites but preferably the Sr sites, and Sm atoms are relatively depleted at the APBs likely owing to the effect of strain.